Análise da proposta de avaliação neuropsicológica de A. R. Luria e suas utilizações contemporâneas - Ricci, Paulo Sérgio Pereira (2014)
The present research is about the Neuropsychological Evaluation proposed by Luria and has a theoretical, analytical and conceptual nature. The objective is to understand the project of Neuropsychological Evaluation and analyze its contemporary uses. Luria (1902-1977) was a Soviet theoretical, maker of Historical-Cultural Psychology. He has a fundamental importance both for Psychology, and for Neuropsychology, and is considered the "father" of Soviet/Russian Neuropsychology. Through this work we seek to understand the project undertaken by Luria in the construction of Neuropsychology related to the needs of his time, from an analysis by the Historical Materialism and Dialectical method. From this, we discuss the current productions in Neuropsychology that uses instrumental evaluation based on Luria, as well as whether the researches that are based on Luria, specifically in the area of Neuropsychological Evaluation are consistent with the principles defended by the author. Such analysis was based on a search on contemporary articles held in the BVS-Psi and LILACS from keywords: Luria and Neuropsychological Evaluation. It is understood that when one distances from Luria's Neuropsychological Evaluation, from a more general project, the preparation of the Historical-Cultural Psychology, risks of performing a cutout in the author's theory, that distance the ultimate objectives of his referrals of Neuropsychology, and makes the instrumentation incoherent with its proposal. The production context of Luria's Neuropsychology allowed greater access to data on brain damage, especially because of the high rate of patients injured in battle, resulting from the Second World War. Luria, inserted in this context, sought to understand the way in which occurs the relationship between brain and behavior. While doing this work, Luria elaborated forms of evaluation of brain damage entailed by injury, which was beyond mere diagnostic purposes, setting goals that enabled enough information to support rehabilitation procedures of lost psychological functions. In proposing a new understanding of brain functioning, the author overcomes the traditional conceptions, especially the understanding of brain functioning from its historical constitution - filo and ontogenetic. The author was also contrary to the propositions of exclusively quantitative evaluation of human mental functioning, because he believed that this could only be understood through qualitative procedures and individual assessment. This form of evaluation takes into account the particularities of each individual assessed, especially with the clarity level of cultural appropriation of each, systematizing a theoretical corpus for Neuropsychology for an explanatory theory of psychic phenomena and their development.